Integrated multi-trophic aquaculture of the European flat oyster (Ostrea edulis Linnaeus, 1758): A case study from Boka Kotorska Bay (Montenegro) - Nikolić Slađana; Mandić Milica; Pešić Vladimir; Ikica Zdravko; Peraš Ines (Oceanological and Hydrobiological Studies)
Although integrated multi-trophic aquaculture (IMTA) is recognized as a strategy to control and minimize the impact of fish farming on the marine environment, there are still many unknowns when it comes to this type of farming. This paper presents the results of research on the growth of European flat oysters in IMTA and monoculture systems. Growth was monitored at three different sites: near fish cages, 100 m from fish cages, and in a monoculture system, during an 18-month experiment. The highest mortality occurred at the site near the fish cages. At the end of the experiment, all monitored individuals reach commercial size, except for four individuals at the site near the fish cages. There were statistically significant differences in oyster growth with respect to site and period. At the site near the fish cages, oyster growth was significantly lower compared to the growth at the two other sites. The most intense growth of oysters occurred during the spring and early summer period. Our results indicate that the production cycle of oysters in integrated aquaculture and monoculture is quite similar and that sites directly adjacent to fish cages should be avoided for oyster farming.